Check vocabulary for Toefl - Wyatt, Rawdon (Macmillan, 2008)
his workbook provides a resource for students studying towards the TOEFL (Test of English as a Foreign Language) exam, which is an entry requirement for non-native speakers at more than 6000 universities worldwide.